1977
DOI: 10.1007/bf00226623
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural study of embryonic and post-hatching development in the pineal organ of the chicken (brown leghorn, Gallus domesticus)

Abstract: The pineal organ of the chicken was investigated electron microscopically during embryonic and post-hatiching development with special regard to photosensory and secretory features. Throughout the developmental period both pinealocytes and supporting cells, of which the pineal parenchyma is composed, were rich in ribosomes, granular endoplasmic reticulum and mitochondria, but lacked agranular endoplasmic reticulum. The outer segments of pinealocytes barely showed formation of lamellar structures (disks) at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

1980
1980
2003
2003

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…For this purpose, conventional transmission and scanning electron microscopy has been used (cf. Oksche and Vaupel-von Harnack 1966;Oksche and Kirschstein 1969;Oksche et al , 1972Boya and Zamorano 1975;Omura 1977;Calvo 1978, 1980;Matsuo 1984, 1988;Möller and Möller 1990). In these studies, typical photoreceptor cells with regular comb-like arrangements of outer segment membranes have not been identified, although basic sensory structures such as bulbous cilia with associated lamellar complexes have been observed (Menaker and Oksche 1974;Vollrath 1981).…”
Section: Discussionmentioning
confidence: 95%
“…For this purpose, conventional transmission and scanning electron microscopy has been used (cf. Oksche and Vaupel-von Harnack 1966;Oksche and Kirschstein 1969;Oksche et al , 1972Boya and Zamorano 1975;Omura 1977;Calvo 1978, 1980;Matsuo 1984, 1988;Möller and Möller 1990). In these studies, typical photoreceptor cells with regular comb-like arrangements of outer segment membranes have not been identified, although basic sensory structures such as bulbous cilia with associated lamellar complexes have been observed (Menaker and Oksche 1974;Vollrath 1981).…”
Section: Discussionmentioning
confidence: 95%
“…Developmental studies on the avian pineal gland have mostly been based on morphological observations at the light (Renzoni 1970;Calvo and Boya 1978) and electron microscopic (Omura 1977;Calvo and Boya 1979) levels, and include descriptions of the expression patterns of genes such as rhodopsin (Robinson et al 1995), HIOMT (Grechez-Cassiau et al 1995) AA-NAT (Herichova et al 2001) and the transcription factors. Only a limited number of studies aiming to clarify the mechanisms involved in pineal development have been reported (Cameron 1903;Bargmann 1943;Holmgnen 1965).…”
Section: Discussionmentioning
confidence: 99%
“…This has been interpreted as evidence that the avian pineal is transformed from a pineal organ to a 'pineal gland' during ontogeny (Sato 2001), a notion which implies loss of photoreceptor characteristics. However, according to Omura (1977) photoreceptor-like structures gradually become more abundant (or easier to detect) with increasing age in the pineal organ of the brown leghorn chicken. In the Japanese quail, there is an initial decrease in numbers of paraboloids and regular stacks of lamellae after hatching, accompanied by an increase in the numbers of synaptic ribbons, but during later development more developed lamellar whorls appear in the follicular lumen (Ohshima & Hiramatsu 1993).…”
Section: Evidence For Sensory Regression During Ontogenetic Developmentmentioning
confidence: 99%